Pengembangan Diri Manusia Menjadi Sosok Berilmu Sebagai Pelita Moderasi Beragama di Era Media Baru 4.0 - Endro Tri Susdarwono (STAI Terpadu Yogyakarta, 2021)
The understanding of religious moderation must be understood contextually not textually, meaning that moderation in religion in Indonesia is not moderate Indonesia, but a moderate way of understanding in religion because Indonesia has many cultures and customs. This study aims to describe how human self-development becomes a knowledgeable figure as a torch or lamp of religious moderation in the era of new media 4.0. The approach in this study uses a descriptive approach. Without the goal of realizing maslahat, religious moderation will never exist. All religions, laws, and ways of life that exist, were actually born for the sake of realizing maslahat. It is because of this maslahat and this is the only reason, Allah sent down the holy books, sent messengers, and established the laws of the Shari'a. Also, due to this maslahat, the minds of all philosophers, experts and thinkers drain all the legacy of the vast human race. Islam strongly criticizes the attitude of neglecting efforts and the desire to seek benefit on the pretext of tawakal to Allah. In order to find the intended benefits, humans are highly demanded in mastering science and technology as the main prerequisites. Human history is full of various events and events which confirm that humans are always looking for common benefit. A knowledgeable human will be able to understand religious moderation very well. Knowledge that is beneficial to mankind is knowledge that can lead humans to a better life, closer to Allah and not cause damage to the earth.